Toxicokinetics and fate of alpha-terthienyl, a botanical larvicide. - Szenasy, Erica. (University of Ottawa (Canada), 1995)
The fate of the phototoxic phytochemical, $\alpha$-terthienyl ($\alpha$-T), which has been proposed as a novel mosquito larvicide was studied in target and non-target organisms. The lethality of this compound was determined in the laboratory by uniform acute toxicity bioassays using the target mosquito larvae, Aedes atropalpus, and two non-target species. Daphnia magna represented a potentially sensitive non-target organism and Limnephilus indivisus (caddisfly) larvae represented a potentially insensitive non-target species. The mosquito larvae had a lethal concentration for 50% mortality (LC$\sb{50})$ value determined to be 31.97 ppb. However, D. magna showed an order of magnitude more sensitivity towards $\alpha$-T with an LC$\sb{50}$ of 1.74 ppb while L. indivisus larvae showed considerably less sensitivity at 64.76 ppb. The bioaccumulation potential was investigated in the three species by toxicokinetic studies. Initial rates of accumulation by the first compartment were highest for A. atropalpus, followed by D. magna and L. indivisus. A. atropalpus reached a steady state in the second compartment. The accumulation of radiolabeled ($\sp3$H) $\alpha$-T did not plateau in the non-target species. The clearance rate constants were highest for D. magna and lowest for L. indivisus, indicating that the most sensitive species was eliminating $\alpha$-T the fastest, in contrast with previous studies. The results from the above studies, combined with previous field trials, predicted mortality at the applied concentrations. This did not translate into severe impacts in the fate study under natural conditions, probably due to volatilization, presence of dissolved organic matter in the water, and rapid photodegradation of $\alpha$-T. In addition, the microcosms were highly anoxic relative to the natural pools. (Abstract shortened by UMI.)
Keywords: Biology, Ecology.